Mobilizing and supporting a community of practice for scaling sustainable water use in rice production in Ghana - Amankwaa-Yeboah, P.; Oke, Adebayo; Yeboah, S.; Zemadim, Birhanu; Okyere, H.; Akwasi, K.; Fati, A. A.; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on Mixed Farming Systems, 2024)
Rice production is a significant user of global water resources, accounting for approximately 30% of the world's freshwater withdrawals. With the global population projected to reach 9.7 billion by 2050, increasing pressure is being placed on the agricultural sector to reduce its water footprint. This report explores the potential of mobilizing and supporting a community of practice (CoP) to scale efficient water use practices in rice production, promoting sustainable agriculture water use and ensuring food security. A mixed-methods approach was used, combining workshops, focus group discussions, and field visits to mobilize farmers and introduce them to water-efficient irrigation technologies such as alternate wetting and drying (AWD) and tailwater harvesting. Several meetings were conducted at the community level to build a gradual reintegration process and cooperation among farmers interested in watersaving agriculture. Through the workshops, focus group discussions, and field visits, a total of 150 farmers were mobilized and introduced to water-efficient irrigation technologies in the Kumbungu, Ahafo Ano South East and Ahafo Ano South West Districts of Ghana, resulting in increased awareness for subsequent adoption of AWD and tailwater harvesting practices. The community-level meetings facilitated the reintegration and cooperation of farmers and other relevant stakeholders which is supposed to lead to the formation of a functional CoP with a shared vision for agricultural water management. The CoP is intended to become a platform for knowledge sharing, collaboration, and innovation among farmers, researchers, policymakers, and other stakeholders, promoting sustainable agriculture and food security in Ghana.